2012
DOI: 10.1002/hep.24772
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of Niemann-Pick C1-like 1 as a negative regulator of Niemann-Pick C2 protein

Abstract: The hepatic expression of Niemann-Pick C1-like 1 (NPC1L1), which is a key molecule in intestinal cholesterol absorption, is high in humans. In addition to NPC1L1, NiemannPick C2 (NPC2), a secretory cholesterol-binding protein involved in intracellular cholesterol trafficking and the stimulation of biliary cholesterol secretion, is also expressed in the liver. In this study, we examined the molecular interaction and functional association between NPC1L1 and NPC2. In vitro studies with adenovirus-based or plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In the chow-fed mice, the major changes are in the normalization of expressions of various lipid transporters, including intestinal NPC1L1, hepatic NPC1L1 protein and Npc1l1 mRNA, and Abcg8 mRNA, and partial resolution of Abcg5 mRNA. In addition, we also observed a significant increase in NPC2 protein that may be a result of a reduction in NPC1L1 protein (21). In turn, this increase may further augment the ABCG5/G8-mediated cholesterol efflux.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the chow-fed mice, the major changes are in the normalization of expressions of various lipid transporters, including intestinal NPC1L1, hepatic NPC1L1 protein and Npc1l1 mRNA, and Abcg8 mRNA, and partial resolution of Abcg5 mRNA. In addition, we also observed a significant increase in NPC2 protein that may be a result of a reduction in NPC1L1 protein (21). In turn, this increase may further augment the ABCG5/G8-mediated cholesterol efflux.…”
Section: Discussionsupporting
confidence: 51%
“…8, e and f). To further address the significance of the changes in hepatic NPC1L1 expressions, we measured the hepatic Niemann-Pick C2 protein levels as recent reports have suggested that the soluble NPC2 protein also participates in stimulating biliary cholesterol efflux in an ABCG5/G8-dependent manner and that its hepatic and biliary levels are negatively modulated by hepatic NPC1L1 (20,21). We observed a significant 70% reduction in the hepatic NPC2 level in the LdlrϪ/ϪxLcatϩ/ϩ mice, and this was also significantly reversed by 2.2-fold in the LdlrϪ/ϪxLcatϪ/Ϫ mice (Fig.…”
Section: Cholesterol Accumulation In Ldlrϫ/ϫxlcatϩ/ϩ Er Membrane Is Nmentioning
confidence: 99%
“…Immunoblot analyses were performed as described in our previous report with minor modifications. Briefly, liver lysate samples were separated by SDS‐PAGE and transferred to an Immobilon‐P PVDF membrane (Millipore Corp., Bedford, MA) by electroblotting at 15 V for 51 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the human liver can secrete cholesterol into bile, but can also re‐uptake the biliary‐secreted cholesterol. The latter process is mediated by the Niemann‐Pick C1‐Like 1 (NPC1L1) protein, a cholesterol transporter that is expressed on the bile canalicular membrane in humans . Thus, we hypothesized that hepatic NPC1L1 could exacerbate NAFLD, including steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol excretion in bile is counteracted by Nieman-Pick C1-like 1 (NPC1L1) protein on the canalicular membrane while NPC2, a cholesterol-binding protein secreted by the biliary system, is a positive regulator of biliary cholesterol secretion by stimulating ABCG5/G8- mediated cholesterol transport (594). Hepatic NPC1L1 may control cholesterol homeostasis via the downregulation of NPC2 (592). …”
Section: Transport and Excretion Of Specific Substancesmentioning
confidence: 99%